2006
DOI: 10.2337/diabetes.55.04.06.db05-1109
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Changes in Plasma Glucose and Pancreatic β-Cell Function in Latino Women at High Risk for Type 2 Diabetes

Abstract: The purpose of this study was to examine longitudinally the relationship among glucose levels, pancreatic ␤-cell function, and insulin resistance in women at high risk for type 2 diabetes. Oral glucose tolerance tests (OGTTs) and intravenous glucose tolerance tests (IVGTTs) were performed at 15-month intervals for up to 5 years or until fasting plasma glucose exceeded 140 mg/dl in Hispanic women with recent gestational diabetes. Data were analyzed 1) to compare changes in insulin sensitivity, ␤-cell function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
72
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 34 publications
15
72
0
1
Order By: Relevance
“…[1][2][3][4] A vast amount of research involving diabetes and complications is focused on areas such as insulin secretion and resistance, pancreatic beta cells, and maintenance of blood glucose levels. 5,6 of this weakened antioxidant defense, the RBCs of these individuals are more prone to oxidant insult and are believed to be less deformable in comparison to RBCs obtained from healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A vast amount of research involving diabetes and complications is focused on areas such as insulin secretion and resistance, pancreatic beta cells, and maintenance of blood glucose levels. 5,6 of this weakened antioxidant defense, the RBCs of these individuals are more prone to oxidant insult and are believed to be less deformable in comparison to RBCs obtained from healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Women with a history of GDM have up to a 60% chance of progressing to type 2 diabetes within 5 years after pregnancy (1,5), depending on advancing insulin resistance and deterioration of islet function (6,7). Subjects with a history of GDM tend to have a higher BMI (8), an athrogenic lipid profile (8 -10), and evidence of subclinical inflammation (11)(12)(13), all characteristics associated with a state of chronic insulin resistance.…”
mentioning
confidence: 99%
“…This result differs from that of population studies in lowincome Mexicans (5) and Fins from the Botnia Study (6), which showed that progressors initially present increased basal glucose and insulin levels. An intermediate result was reported by Xiang et al (18) in their non-population study of Hispanic women with a recent history of gestational diabetes mellitus, where progressors initially presented elevated fasting blood glucose but fasting insulinemia similar to non-progressors.…”
Section: Comparative Analysis Of Initial Demographic and Metabolic Chmentioning
confidence: 75%
“…Our finding of elevated blood glucose in the second hour of the OGTT can be explained by the reduction in first-phase insulin secretion in the hyperglycemic clamp test. Previous studies (3,18,(28)(29)(30)(31), including ours involving Caucasian Americans (8), have reported that individuals with NGT and at risk for type 2 diabetes mellitus have an insufficient insulin response to intravenous glucose stimulation tests, suggesting that β cell dysfunction could be the first defect involved in type 2 diabetes mellitus pathogenesis.…”
Section: Comparative Analysis Of Initial Demographic and Metabolic Chmentioning
confidence: 99%
See 1 more Smart Citation